Decreasing of hydraulic losses in firefighting centrifugal pumps - Vertjachih Игорь Михайлович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
The analysis of causes of hydraulic and disk losses in centrifugal pumps is carried out. The ways of decreasing the losses is shown. The influence of polymer covering on the friction process of disk samples in working liquid was investigated. The authors also substantiate the possibility of increasing efficiency of firefighting centrifugal pump by means of decreasing hydraulic and disk losses by covering their working wheel and pipes with polymer.